Mitologi Perkawinan Dayak Tobag - Seko, Salfius; Soa, Alfonsus Hendri; Negara, Purnawan Dwikora (Widya Yuridika, 2024)
This article reviews the implementation of the marriage traditions of the Dayak Tobag traditional community in Tayan Hilir District, Sanggau Regency from a socio-anthropological perspective which is still maintained today. The aim is to identify, describe and explain marriages in the Tobag Dayak sub-tribe from a socio- anthropological perspective in Tebang Benua Village, Tayan Hilir District using empirical legal research methods to see the types of traditional marriages carried out by the Tobag Dayak indigenous community. Indigenous peoples often have deep reasons for maintaining traditional marriages and rituals. Indigenous peoples tend to highly value their traditions and cultural heritage. Weddings and traditional rituals are an integral part of their cultural identity that has been passed down from generation to generation. Maintaining traditions is considered a way to honor ancestors and maintain the integrity of their culture. From the results of this research it can be revealed that there are 4 types of Tobag Dayak traditional marriage ceremonies, namely: hanging marriage customs, simple marriage customs, ordinary marriage customs, and large wedding customs